Effect of Soil Bulk Density on Wetting Front AdvanceUnder a Trickle Line Source - T. Abdul-Baki, Yousra; A. Sulaiman, Zeyad; I. Yasin, Haqqi (Anbar Journal of Engineering Science, 2010)
The movement of water in the soil are affected by many factors including: the soil structure and texture, the flow rate , the volume of application water ,application method (continuous or intermittent), initial water content of the soil, and temperature of water and soil. The bulk density of surface soil or sub surface soil will be changed due to tillage or compaction operations , so the research aims to study the effect of bulk density on the advance of the wetting front under trickle irrigation. The experiment Included 9 tests for monitoring the advance of the wetting front with time, during the water application phase and water redistribution phase, using three cases of provider soil densities virtual amount of 1.35 and 1.45 and 1.55 g / cm 3, using three flow rates 0.675, 1.350, 2.700 cm 3 / min / cm. The study showed that the horizontal advance increases and the vertical advance decreases with the increase in bulk density, although the decrease in the vertical advance is greater than the increase in the horizontal advance with the increase in bulk density of soil profile during the water application phase. The study also demonstrated that the percentage of change both the horizontal advance and the vertical advance through water redistribution phase relative to the value of each of them at the end of the water application phase are 27.2% and 35.1% respectively, and there is no effect to change the bulk density of the soil profile on these ratios. The study clarified that the percentage of change both the horizontal advance and the vertical advance through the water redistribution phase relative to the value of each of them at the end of water application phase increases with the decrease in the flow rate. And the degree of increase in the vertical advance roughly constant, while there is decrease by the increase in the horizontal advance with the increase in flow rate the water redistribution phase.